Interacting environmental mosaics drive geographic variation in mussel performance and predation vulnerability. (6th May 2016) - Kroeker, Kristy J.; Sanford, Eric; Rose, Jeremy M.; Blanchette, Carol A.; Chan, Francis; Chavez, Francisco P.; Gaylord, Brian; Helmuth, Brian; Hill, Tessa M.; Hofmann, Gretchen E.; McManus, Margaret A.; Menge, Bruce A.; et al.
Abstract: Although theory suggests geographic variation in species' performance is determined by multiple niche parameters, little consideration has been given to the spatial structure of interacting stressors that may shape local and regional vulnerability to global change. Here, we use spatially explicit mosaics of carbonate chemistry, food availability and temperature spanning 1280 km of coastline to test whether persistent, overlapping environmental mosaics mediate the growth and predation vulnerability of a critical foundation species, the mussel Mytilus californianus . We find growth was highest and predation vulnerability was lowest in dynamic environments with frequent exposure to low pH seawater and consistent food. In contrast, growth was lowest and predation vulnerability highest when exposure to low pH seawater was decoupled from high food availability, or in exceptionally warm locations. These results illustrate how interactions among multiple drivers can cause unexpected, yet persistent geographic mosaics of species performance, interactions and vulnerability to environmental change.